Perancangan Sistem Informasi Arsip Data Kelahiran dengan Metode Waterfall Berbasis Website - Oktavianus Leu; Nani Suningrat; Wasis Haryono (CV. Multi Kreasi Media, 2024)
In the digital era, efficient management of birth certificate archives is essential to improve public services. The Tangerang District Population and Civil Registration Office has a big responsibility in providing and managing population data. However, the manual process that is still used often causes loss of documents, difficulty searching for data, and slow service. This research aims to design and implement a website-based Birth Certificate Archive Information System for the Population and Civil Registration Office of Tangerang Regency. The Waterfall method was used as a system development approach, including the stages of analysis,design, implementation, testing, and maintenance. The results show that this website-based system can simplify archiving, speed up data searches, and reduce dependence on physical documents. Black Box testing ensures the system functions according to user needs. This system is expected to have a positive impact in improving the efficiency of archive management, supporting document digitization, and improving the quality of public services.